Sustaining the environment: a case study of the garment industry in Bangladesh - Islam, Md Nazrul; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2021)
Introduction: Garment industry is one of the leading manufacturing sectors and plays a significant role in improving social, financial impact, building employment and exporting in developed economies in Bangladesh. Nevertheless, textiles are accused of being one of the most genetically dangerous industries, especially to the environment because it also produces waste, not just for clothing production and use. Thus, many scholars have recognized how important it is to explore a better environment for effective utilization in these sectors. Objective: This review paper explores the Garment industry's sustainability environment's evolution and examined how its Management can play a pioneering role in staying so long. Method: This review paper involved with secondary data which are collected from journal, proceedings, books and social media using the keywords of “garment industry” and “sustainable waste management and strategies in the garments industry”. Articles with key words in its titles or abstract were selected. This was done for articles published mainly in 2015-2020. Results: In mitigating its adverse environmental impacts, the textile company has made many measures to counter it. Each of these measures is the recycling and replication of waste fibers. Recycling methods may be used with thermal and biological techniques. Textile processing improves sustainable health and decreases the market for technical textiles, eliminates waste requirements, reduces energy demand and water emissions. Conclusion: Sustainable Waste Management and Strategies is very crucial in the garments Industry. Thus, advertising plans and procedures must improve consumer loyalty and encourage manufacturers' use of recycled waste in new products.